Frequency of Monitoring Hemoglobin A1C and Achieving Diabetes Control - Augusto F. Parcero MD; Thomas Yaeger MD; Robert S. Bienkowski PhD (SAGE Publishing, 2011)
Objectives: The American Diabetes Association recommends measuring hemoglobin A1C levels (A1C) at least semiannually in diabetic patients who have stable glycemic control and quarterly in patients whose therapy has changed or who are not meeting glycemic goals. These guidelines were based on expert consensus without reference to actual clinical data. The main objective of this study was to assess association between meeting a target A1C level of <7% and adherence to monitoring guidelines. Secondary objectives were to determine the proportion of diabetic patients in the authors' practice who met the A1C monitoring guidelines and to assess whether meeting the target A1C level is associated with other information easily abstracted from patients records, namely age, gender, and types of therapy. Methods: This study employed a case control design. Records of 193 type 2 diabetic patients seen over a 6-month period in a rural family medicine clinic were analyzed. Assessment of diabetes control was based on the most recent A1C level, with <7% considered controlled. Adherence to guidelines was assessed by determining frequency of testing during the preceding 12-month period. Results: Ninety-eight patients (51%) adhered to the American Diabetes Association guidelines on frequency of monitoring A1C. Median levels of adherent and nonadherent patients differed significantly (6.5 vs 7.3, P < .001, Mann-Whitney test). Logistic regression analysis showed that "diabetes control" based on the A1C level is positively associated with adherence to the guidelines, negatively associated with intensity of therapy, and not associated with gender or age. Conclusion: This study supports the usefulness of American Diabetes Association practice guidelines on the frequency of monitoring A1C levels in diabetic patients.